Metode Pembelajaran Menggunakan Studi Kasus, Karya Wisata, Praktikum dan Eksperimen - Anggi Widya; Fitria Ghaida Nur Rahma; Dinda Nurul Wahidiyah; Annysa Gea Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Education plays an important role in improving the quality of a country's human resources. Therefore, the use of various learning methods is very important, especially to maximize the student learning process. This article discusses the effectiveness of learning methods using case studies, field trips, practicums and experiments in improving student learning outcomes and increasing student motivation in the learning process. This research uses a descriptive method with data collection techniques through interviews, observation and documentation. Learning methods using case studies and field trips provide direct experience for students and can significantly influence student involvement in the learning process. Likewise, practical and experimental methods provide direct experience in using theory in practice. However, implementing this method requires careful planning and quite a lot of money. Apart from that, teachers also play an important role in classroom management and providing the necessary guidance during the learning process. The use of various effective learning methods is expected to improve the quality of a country's education and produce quality human resources. Therefore, there needs to be support from various parties to apply this learning method in order to create a better and more qualified generation.